Experimental and computational investigation on the binding of anticancer drug gemcitabine with bovine serum albumin. Issue 19 (15th November 2022) - Ali, Mohd Sajid; Muthukumaran, Jayaraman; Jain, Monika; Al-Lohedan, Hamad A.; Farah, M. Abul; Alsowilem, Osama Ibrahim
Abstract: This study reports the experimental and computational investigation on the binding of a common anticancer drug, gemcitabine, with the model plasma protein, bovine serum albumin (BSA). Several experimental and computational methods, such as intrinsic and synchronous fluorescence, UV-visible, and circular dichroism spectroscopies, consensus molecular docking and molecular dynamics simulation have been employed to elucidate the binding mechanism. Gemcitabine altered the UV-visible spectrum of BSA, which is a clear indication of the complex formation between them. The visual inspection of observed fluorescence quenching results at λex = 280 nm and 295 nm has shown the substantial involvement of tyrosine residue, even larger than tryptophan. However, after the correction of inner filter effect of the observed data, it became clear that tyrosine has a negligible role in quenching. A 20-fold decrease in quenching constant was found in the corrected data, as compared to the observed data at λex = 280 nm. There was a 1:1 weak binding between BSA and gemcitabine accompanied by dynamic quenching. The secondary structure of BSA remained almost intact in the presence of gemcitabine. The primary binding site of gemcitabine inside BSA was the drug binding site 2 or DS II, which is located in the subdomain 3 A. MD Simulation results suggested that gemcitabine doesn't affect or deviate the structure of BSA upon interaction throughout 100 ns time period. The dominating intermolecular forces were hydrophobic forces and hydrogen bonding. A small change in the frontier molecular orbitals of gemcitabine was also observed after its binding with BSA. Communicated by Ramaswamy H. Sarma